Analisis Sistem Informasi Akuntansi Penagihan Termyn Pada Penjualan Jasa Kontruksi : Studi Kasus CV. Salamun Karya Utama - Mela Endriani; Fitri Komariyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
CV. Salamun Karya Utama is a company engaged in the construction of finishing architectural buildings, in the process of selling services the company participates in various kinds of BUMN and private tenders. The author conducted this study aims to analyze the information system stages of sales of construction services at CV service companies. Greetings Main Works. The method used in this research is a qualitative descriptive analysis method with interview and observation techniques. Stages of accounting information system sales of services at a construction company CV. Salamun Karya Utama is still done manually and has not adhered to modern accounting it makes internal control weaknesses within the company, the author suggests adding workers according to their respective sections so that no one does double job disk so that it can support the company's performance